Islam in contemporary Africa: re-reading history, contemplating challenges (2016)
This paper is hinged on the following propositions: that any inquiry into the problematic of Islam in contemporary Africa must engage, not only with how the past has shaped the present, but equally with how the latter would likely shape and, in turn, be -shaded by possibilities in the future; that contemporary challenges facing Islam in Africa nests, in the main, in the disconnect between Islam in the text and the fissures in the contexts of Muslim realities all over the world. In exploring these assumptions, this paper casts a fresh look at the history and the unassailable patrimonies of Islam in the continent. It proceeds from there to explore some of the challenges facing the religion in the continent. While projecting into the future, the paper sources its discussion from critical perspectives that have been offered by, among others, Ali Mazrui, Sayyid Hussein Nasr and Talal Asad among others.